Idiopathic plasma cell balanitis of Zoon in a 15-year-old boy. - Mir-Bonafé, J.M.; Romo-Melgar, A.; Santos-Briz, Á.; Fernández López, E.A. (European Journal of Pediatric Dermatology, 2012)
We report a 15-year-old boy with lesions mainly involving glans penis and prepuce, which appeared 4 years before. Histopathological study showed representative features of plasma cell balanitis of Zoon confirming this diagnosis. He presented a favorable outcome under topical tacrolimus 0.1%. The occurrence of this entity during childhood is extremely rare.